DAUN KELOR (MORINGA OLEIFERA) UNTUK MENINGKATKAN KADAR HAEMOGLOBIN PADA IBU HAMIL: A LITERATUR REVIEW - Evi Irianti (Poltekkes Kemenkes Medan, 2020)
Introduction: Pregnancies by anemia, if not handled seriously be able to cause a high degree of caused the birth low weight of baby even till maternal mortality. Kelor leaves containing nutrients such as macro, carbohydrates, proteins and micronutrient (vitamin E, calcium, iron, zinc, vitamin C etc.) is needed especially by pregnant women. Methods: This research method is a literature review based on electronic data that is 5 pieces original research. Results and Discussion: Consumtion of Moringa oliefera leaves extracts or flour that is inserted into the capsules still have a useful efficacy to increase the haemoglobin levels of anemia in pregnant significantly, so also if they are consumed directly as vegetables. This is because they cointan iron, high vitamin C so that it can help to increase the heme as a booster of haemoglobin in the blood.. Conclusion: Giving Moringa oliefera leaves to pregnancy as a processed food or vegetable helps to increase the haemoglobin, therefore advised introducing to public to consume them, especially for pregnancies as supplements besides Fe tablets.